Lignite-based modified filtrate reducer for drilling fluid and preparation method of lignite-based modified filtrate reducer

By using lignite-based modified filtration loss reducer in drilling fluid, combined with technical means of modifying benzooxazine monomer, zwitterionic monomer and nanosilicon dioxide, the problem of insufficient salt resistance of the existing filtration loss reducer under high salt conditions is solved, and the efficient filtration loss reduction effect is achieved under high temperature and high salt conditions.

CN119842369AInactive Publication Date: 2025-04-18SHANDONG DESHUNYUAN PETROLEUM SCI&TECH CO LTD

Patent Information

Application Number
CN202510338755.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Humic acid filtration loss-reducing agents in existing drilling fluids are insufficient in salt resistance under high salt conditions, making it difficult to be suitable for drilling fluids with high salt content.

Method used

By stirring and mixing the lignite graft copolymer, hydroxypropyl cellulose and graphene oxide, and pulverizing it after drying, a lignite-based modified filtration reduction agent for drilling fluid was prepared. The filter reduction agent improves its mild salt resistance by introducing modified benzooxazine monomers, zwitterionic monomers and nanosilicon dioxide.

Benefits of technology

The modified filter reduction loss agent exhibits good temperature and salt resistance under high temperature and high salt conditions, effectively reducing the filtration loss of drilling fluid, improving the stability of the well wall and reservoir protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842369A_ABST
    Figure CN119842369A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of drilling fluids, and discloses a lignite-based modified filtrate reducer for a drilling fluid and a preparation method of the lignite-based modified filtrate reducer. The lignite-based modified filtrate reducer for the drilling fluid is obtained by stirring and mixing the lignite grafted copolymer, the hydroxy propyl cellulose and the graphene oxide, drying and crushing. The steric effect generated by an oxazine ring, a pyridine ring, a triazine ring, a benzene ring and a pyrrole ring grafted into the lignite improves the temperature resistance and salt resistance of the filtrate reducer; the dispersing capacity of clay particles in a drilling fluid system is improved through sulfonic acid hydrated groups, and high-temperature coalescence of drilling fluid clay due to the high-temperature effect is avoided; a sulfonic acid anion group and a quaternary ammonium salt cation group are introduced into the filtrate reducer at the same time, so that the filtrate reducer can form a salt internal bond under the action of electrostatic force, and the salt resistance of the filtrate reducer is improved; the nano silicon dioxide increases the rigidity of the filtrate reducer, so that the filtrate reducer is not easy to curl under the conditions of high temperature and high salt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of drilling fluid, in particular to a lignite-based modified fluid loss reducer for drilling fluid and a preparation method thereof. Background Art

[0002] In oil and gas drilling projects, drilling fluid, as the "blood", undertakes core functions such as stabilizing the well wall, carrying cuttings, and balancing formation pressure. Among them, fluid loss reducer is a key treatment agent for drilling fluid. By reducing the penetration of filtrate into the formation, it can effectively prevent well wall collapse, reservoir damage and uncontrolled rheology of drilling fluid. Humic acid fluid loss reducer is one of the most widely used treatment agents in oilfield chemicals. Lignite is a type of coal containing 20%-80% humic acid and is the main source of humic acid. Humic acid molecules usually contain a variety of functional groups, including carboxyl, methoxy, alcohol hydroxyl, phenolic hydroxyl and carbonyl. It is precisely because of these functional groups in humic acid molecules that humic acid has good fluid loss reduction and viscosity reduction properties. It is widely used as a fluid loss reducer and viscosity reducer for high-temperature deep well drilling fluids, but its salt tolerance is poor and it is generally only applicable to freshwater drilling fluids or drilling fluids with low salt content. The document "Synthesis and Evaluation of Fluid Loss Reducer AMPS / AM / Sodium Humate" uses lignite as raw material to produce sodium humate, and then uses 2-acrylamido-2-methylpropanesulfonic acid, acrylamide and sodium humate as monomers to synthesize a copolymer fluid loss reducer. The copolymer has good fluid loss reduction ability in fresh water-based slurry, and exhibits good temperature resistance when the copolymer addition amount is greater than 1.0%, but its salt resistance needs to be improved. Summary of the invention

[0003] 1. Technical issues to be resolved In view of the shortcomings of the prior art, the present invention provides a lignite-based modified fluid loss reducer for drilling fluid and a preparation method thereof. The fluid loss reducer prepared by the present invention has good temperature resistance and salt resistance.

[0004] (II) Technical solution To achieve the above object, the present invention provides the following technical solution: a lignite-based modified fluid loss reducer for drilling fluid, comprising the following components by weight: 14-18 parts by weight of lignite graft copolymer, 1.2-1.8 parts by weight of hydroxypropyl cellulose, and 0.2-0.4 parts by weight of graphene oxide.

[0005] Preferably, the method for preparing the lignite graft copolymer comprises the following steps: (1) Add 10-12 g of 2-alkenyl-4-aminopyridine and 5.6-6.2 g of polyformaldehyde to 50-70 mL of toluene solvent, react at 30-38° C. for 0.5-1 h, add 10.8-12.4 g of p-hydroxybenzaldehyde, heat to 75-85° C. and reflux for 4-7 h. After the reaction, wash with a sodium hydroxide aqueous solution having a mass fraction of 4%-4.5%, and remove the solvent by rotary evaporation to obtain intermediate 1; (2) Add 2.1-2.5 g of melamine, 6.5-7.5 g of intermediate 1, and 2.8-3.2 g of a dehydrating agent to 35-50 mL of methanol solvent, introduce nitrogen protection, heat to 105-115° C. and react for 3-6 hours. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a modified benzoxazine monomer; (3) 30-60 mL of anhydrous ethanol and 10-20 mL of deionized water are mixed as a solvent, 7.6-10.4 g of N-ethyl-3-trimethoxysilane-2-methylpropylamine is added thereto, ultrasonic dispersion is performed for 30-50 min, 2.4-3 mL of hydrochloric acid solution is added to adjust the pH value to 4-5, 1.8-2.6 g of nano-silica is added, ultrasonic dispersion is performed for 1-1.5 h, the temperature is raised to 70-80 ° C and refluxed for reaction for 2-6 h, after the reaction is completed, the mixture is washed with anhydrous ethanol, filtered and dried to obtain secondary amine nano-silica; (4) Add 8-12 g of N-vinyl pyrrolidone, 5-7 g of polyformaldehyde, and 0.02-0.05 g of a catalyst to 70-80 mL of anhydrous ethanol solvent, stir and mix, introduce nitrogen for 30-50 min to deoxygenate, heat to 88-94° C., add 4.2-5 g of secondary amine nano-silica, continue to heat to 135-145° C. and react for 6-10 h. After the reaction is completed, remove the solvent by rotary evaporation to obtain tertiary amine nano-silica modified pyrrolidone; (5) Add 4.5-6.5 g of 1,3-propane sultone to 45-65 mL of acetone solvent, stir and dissolve at 28-32° C., dissolve 3.2-4.8 g of tertiary amine nano-silica-modified pyrrolidone in 20-30 mL of acetone, and add it dropwise to the 1,3-propane sultone solution. After the addition is complete, heat to 35-40° C. and react for 3.5-5 hours. After the reaction is complete, filter and dry to obtain a zwitterionic monomer; (6) Add 10-18 mL of lignite alkali solution, 0.8-1.4 g of acrylamide, 0.5-0.8 g of modified benzoxazine monomer, and 0.4-0.6 g of zwitterionic monomer into a flask, stir and mix, introduce nitrogen for 10-15 min to deoxygenate, raise the temperature to 48-54°C, add 0.07-0.09 g of ammonium persulfate, continue to raise the temperature to 62-70°C, react for 2-3 h, and after the reaction is completed, obtain a lignite graft copolymer.

[0006] Preferably, the dehydrating agent in step (2) is anhydrous sodium sulfate.

[0007] Preferably, the mass fraction of the hydrochloric acid solution in step (3) is 2.6%-3%.

[0008] Preferably, the catalyst in step (4) is acetic acid.

[0009] Preferably, the dripping time of the tertiary amine-based nano-silica-modified pyrrolidone in step (5) is 30-45 minutes.

[0010] Preferably, the preparation method of the lignite alkali solution in step (6) is: add 10-15 g of lignite to 20-30 mL of a sodium hydroxide solution with a mass fraction of 4.8%-5.2%, heat to 80-95° C., stir for 1-2 h, and then filter to remove insoluble residue to obtain the lignite alkali solution.

[0011] Preferably, the preparation method of the lignite-based modified fluid loss reducer for drilling fluid is: add lignite graft copolymer, hydroxypropyl cellulose and graphene oxide into a reactor, stir and mix at 700-900 rpm for 12-20 min, dry in a drying oven at 68-72° C. and then crush to obtain the lignite-based modified fluid loss reducer for drilling fluid.

[0012] 3. Beneficial technical effects The invention obtains a lignite-based modified fluid loss reducer for drilling fluid by stirring and mixing lignite graft copolymer, hydroxypropyl cellulose and graphene oxide, drying and then crushing the mixture.

[0013] The steric hindrance effect of the rigid groups of the oxazine ring, pyridine ring, triazine ring, benzene ring in the modified benzoxazine monomer grafted into lignite and the pyrrole ring in the zwitterionic monomer is conducive to the stretching of the molecular chain, prompting the polymer to form a dense spatial network structure in the drilling fluid, and can limit the hydrolysis of the amide group on the main chain, thereby improving the temperature and salt resistance of the fluid loss reducer; the sulfonic acid hydration group not only increases the solubility of the fluid loss reducer in water, but also can form a thick hydration film on the surface of the clay particles, increasing the dispersion of the clay particles in the drilling fluid system, avoiding the high-temperature agglomeration of the drilling fluid clay due to high temperature, resulting in an increase in the filtration loss, and improving the high-temperature resistance of the fluid loss reducer; if the fluid loss reducer contains only one charged ion, the electrostatic repulsion within its molecules will be reduced due to the invasion of electrolytes. , causing the molecular chain of the fluid loss reducer to curl and not be well adsorbed with clay particles. The simultaneous introduction of sulfonic acid anion groups and quaternary ammonium salt cation groups into the fluid loss reducer can make the fluid loss reducer form salt bonds under the action of electrostatic force and form molecular associations inside the fluid loss reducer. When electrolytes invade, the salt bonds are first destroyed, making the originally curled molecular chains stretch, increasing the adsorption of clay particles, reducing the filtration loss of the drilling fluid system, and thus improving the salt resistance of the fluid loss reducer. Introducing nano-silicon dioxide into the fluid loss reducer increases the rigidity of the fluid loss reducer, making it less likely to curl under high temperature and high salt conditions, and the silanol groups on the surface of nano-silicon dioxide and the silanol groups on the surface of bentonite are prone to dehydration condensation reactions, which increases the binding force between the bentonite particles and the fluid loss reducer, making it less likely to desorb at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is the synthetic reaction formula of modified benzoxazine monomer.

[0015] Figure 2 It is the synthetic reaction formula of zwitterionic monomer. DETAILED DESCRIPTION Example 1

[0016] (1) Add 10 g of 2-alkenyl-4-aminopyridine and 5.6 g of polyformaldehyde to 50 mL of toluene solvent, react at 30°C for 0.5 h, add 10.8 g of p-hydroxybenzaldehyde, heat to 75°C and reflux for 4 h. After the reaction, wash with 4% sodium hydroxide aqueous solution, and remove the solvent by rotary evaporation to obtain intermediate 1; (2) Add 2.1 g of melamine, 6.5 g of intermediate 1, and 2.8 g of anhydrous sodium sulfate dehydrating agent to 35 mL of methanol solvent, introduce nitrogen protection, heat to 105 ° C and react for 3 h. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a modified benzoxazine monomer; (3) 30 mL of anhydrous ethanol and 10 mL of deionized water were mixed as a solvent, 7.6 g of N-ethyl-3-trimethoxysilane-2-methylpropylamine was added thereto, and ultrasonic dispersion was performed for 30 min. 2.4 mL of a 2.6% hydrochloric acid solution was added to adjust the pH value to 4, 1.8 g of nano-silica was added, and ultrasonic dispersion was performed for 1 h. The mixture was heated to 70 °C and refluxed for 2 h. After the reaction was completed, the mixture was washed with anhydrous ethanol, filtered and dried to obtain secondary amine nano-silica. (4) Add 8 g of N-vinyl pyrrolidone, 5 g of polyformaldehyde, and 0.02 g of acetic acid catalyst to 70 mL of anhydrous ethanol solvent, stir and mix, introduce nitrogen for 30 min to deoxygenate, heat to 88 ° C, add 4.2 g of secondary amine nano-silica, continue to heat to 135 ° C to react for 6 h, and after the reaction is completed, remove the solvent by rotary evaporation to obtain tertiary amine nano-silica modified pyrrolidone; (5) Add 4.5 g of 1,3-propane sultone to 45 mL of acetone solvent, stir and dissolve at 28 °C, dissolve 3.2 g of tertiary amine nano-silica-modified pyrrolidone in 20 mL of acetone, and add it dropwise to the 1,3-propane sultone solution for 30 min. After the addition is complete, heat to 35 °C and react for 3.5 h. After the reaction is complete, filter and dry to obtain a zwitterionic monomer; (6) Add 10 g of lignite to 20 mL of 4.8% sodium hydroxide solution, heat to 80 °C and stir for 1 h, then filter out the insoluble residue to obtain lignite alkali solution; (7) Add 10 mL of lignite alkali solution, 0.8 g of acrylamide, 0.5 g of modified benzoxazine monomer, and 0.4 g of zwitterionic monomer into a flask, stir and mix, introduce nitrogen for 10 min to deoxygenate, heat to 48 °C, add 0.07 g of ammonium persulfate, continue to heat to 62 °C and react for 2 h. After the reaction is completed, a lignite graft copolymer is obtained; (8) 14 parts by weight of lignite graft copolymer, 1.2 parts by weight of hydroxypropyl cellulose, and 0.2 parts by weight of graphene oxide were added to a reactor, and the mixture was stirred at 700 rpm for 12 min. The mixture was dried in a drying oven at 68° C. and then crushed to obtain a lignite-based modified fluid loss reducer for drilling fluid. Example 2

[0017] (1) Add 12 g of 2-alkenyl-4-aminopyridine and 6.2 g of polyformaldehyde to 70 mL of toluene solvent, react at 38°C for 1 h, add 12.4 g of p-hydroxybenzaldehyde, heat to 85°C and reflux for 7 h. After the reaction, wash with 4.5% sodium hydroxide aqueous solution, and remove the solvent by rotary evaporation to obtain intermediate 1; (2) Add 2.5 g of melamine, 7.5 g of intermediate 1, and 3.2 g of anhydrous sodium sulfate dehydrating agent to 50 mL of methanol solvent, introduce nitrogen protection, heat to 115 ° C. and react for 6 h. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a modified benzoxazine monomer; (3) 60 mL of anhydrous ethanol and 20 mL of deionized water were mixed as a solvent, 10.4 g of N-ethyl-3-trimethoxysilane-2-methylpropylamine was added thereto, and ultrasonic dispersion was performed for 50 min. 3 mL of a 3% hydrochloric acid solution was added to adjust the pH value to 5, 2.6 g of nano-silica was added, and ultrasonic dispersion was performed for 1.5 h. The mixture was heated to 80 °C and refluxed for 6 h. After the reaction was completed, the mixture was washed with anhydrous ethanol, filtered and dried to obtain secondary amine nano-silica. (4) Add 12 g of N-vinyl pyrrolidone, 7 g of polyformaldehyde, and 0.05 g of acetic acid catalyst to 80 mL of anhydrous ethanol solvent, stir and mix, introduce nitrogen for 50 min to deoxygenate, heat to 94 ° C, add 5 g of secondary amine nano-silica, continue to heat to 145 ° C to react for 10 h, and after the reaction is completed, remove the solvent by rotary evaporation to obtain tertiary amine nano-silica modified pyrrolidone; (5) Add 6.5 g of 1,3-propane sultone to 65 mL of acetone solvent, stir and dissolve at 32 °C, dissolve 4.8 g of tertiary amine nano-silica-modified pyrrolidone in 30 mL of acetone, and add it dropwise to the 1,3-propane sultone solution for 45 min. After the addition is complete, heat to 40 °C and react for 5 h. After the reaction is complete, filter and dry to obtain a zwitterionic monomer. (6) Add 15 g of lignite to 30 mL of 5.2% sodium hydroxide solution, heat to 95 °C and stir for 2 h, then filter out the insoluble residue to obtain lignite alkali solution; (7) Add 18 mL of lignite alkali solution, 1.4 g of acrylamide, 0.8 g of modified benzoxazine monomer, and 0.6 g of zwitterionic monomer into a flask, stir and mix, introduce nitrogen for 15 min to deoxygenate, heat to 54 °C, add 0.09 g of ammonium persulfate, continue to heat to 70 °C and react for 3 h. After the reaction is completed, a lignite graft copolymer is obtained; (8) 18 parts by weight of lignite graft copolymer, 1.8 parts by weight of hydroxypropyl cellulose, and 0.4 parts by weight of graphene oxide were added to a reactor, stirred and mixed at 900 rpm for 20 min, dried in a drying oven at 72° C., and then crushed to obtain a lignite-based modified fluid loss reducer for drilling fluid. Example 3

[0018] (1) Add 11 g of 2-alkenyl-4-aminopyridine and 5.9 g of polyformaldehyde to 60 mL of toluene solvent, react at 34 °C for 0.7 h, add 11.6 g of p-hydroxybenzaldehyde, heat to 80 °C and reflux for 5.5 h. After the reaction, wash with 4.2% sodium hydroxide aqueous solution, and remove the solvent by rotary evaporation to obtain intermediate 1; (2) Add 2.3 g of melamine, 7 g of intermediate 1, and 3 g of anhydrous sodium sulfate dehydrating agent to 42 mL of methanol solvent, introduce nitrogen protection, heat to 110° C. and react for 4.5 h. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a modified benzoxazine monomer; (3) 45 mL of anhydrous ethanol and 15 mL of deionized water were mixed as a solvent, 9 g of N-ethyl-3-trimethoxysilane-2-methylpropylamine was added thereto, and ultrasonic dispersion was performed for 40 min. 2.7 mL of a 2.8% hydrochloric acid solution was added to adjust the pH value to 4.5, 2.2 g of nano-silica was added, and ultrasonic dispersion was performed for 1.2 h. The mixture was heated to 75 °C and refluxed for 4 h. After the reaction was completed, the mixture was washed with anhydrous ethanol, filtered and dried to obtain secondary amine nano-silica. (4) Add 10 g of N-vinyl pyrrolidone, 6 g of polyformaldehyde, and 0.04 g of acetic acid catalyst to 75 mL of anhydrous ethanol solvent, stir and mix, introduce nitrogen for 40 min to deoxygenate, heat to 91 ° C, add 4.6 g of secondary amine nano-silica, continue to heat to 140 ° C to react for 8 h, and after the reaction is completed, remove the solvent by rotary evaporation to obtain tertiary amine nano-silica modified pyrrolidone; (5) Add 5.5 g of 1,3-propane sultone to 55 mL of acetone solvent, stir and dissolve at 30 °C, dissolve 4 g of tertiary amine nano-silica-modified pyrrolidone in 25 mL of acetone, and add it dropwise to the 1,3-propane sultone solution for 38 min. After the addition is complete, heat to 38 °C and react for 4.2 h. After the reaction is complete, filter and dry to obtain a zwitterionic monomer; (6) Add 12.5 g of lignite to 25 mL of 5% sodium hydroxide solution, heat to 88 °C and stir for 1.5 h, then filter out the insoluble residue to obtain lignite alkali solution; (7) Add 14 mL of lignite alkali solution, 1.1 g of acrylamide, 0.6 g of modified benzoxazine monomer, and 0.5 g of zwitterionic monomer into a flask, stir and mix, introduce nitrogen for 12 min to deoxygenate, heat to 51 °C, add 0.08 g of ammonium persulfate, continue to heat to 66 °C and react for 2.5 h. After the reaction is completed, a lignite graft copolymer is obtained; (8) 16 parts by weight of lignite graft copolymer, 1.5 parts by weight of hydroxypropyl cellulose, and 0.3 parts by weight of graphene oxide were added to a reactor, and the mixture was stirred at 800 rpm for 16 min. The mixture was dried in a drying oven at 70° C. and then crushed to obtain a lignite-based modified fluid loss reducer for drilling fluid. Example 4

[0019] (1) Add 10 g of 2-alkenyl-4-aminopyridine and 5.6 g of polyformaldehyde to 50 mL of toluene solvent, react at 30°C for 0.5 h, add 10.8 g of p-hydroxybenzaldehyde, heat to 75°C and reflux for 4 h. After the reaction, wash with 4% sodium hydroxide aqueous solution, and remove the solvent by rotary evaporation to obtain intermediate 1; (2) Add 2.1 g of melamine, 6.5 g of intermediate 1, and 2.8 g of anhydrous sodium sulfate dehydrating agent to 35 mL of methanol solvent, introduce nitrogen protection, heat to 105 ° C and react for 3 h. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a modified benzoxazine monomer; (3) 30 mL of anhydrous ethanol and 10 mL of deionized water were mixed as a solvent, 7.6 g of N-ethyl-3-trimethoxysilane-2-methylpropylamine was added thereto, and ultrasonic dispersion was performed for 30 min. 2.4 mL of a 2.6% hydrochloric acid solution was added to adjust the pH value to 4, 1.8 g of nano-silica was added, and ultrasonic dispersion was performed for 1 h. The mixture was heated to 70 °C and refluxed for 2 h. After the reaction was completed, the mixture was washed with anhydrous ethanol, filtered and dried to obtain secondary amine nano-silica. (4) Add 12 g of N-vinyl pyrrolidone, 7 g of polyformaldehyde, and 0.05 g of acetic acid catalyst to 80 mL of anhydrous ethanol solvent, stir and mix, introduce nitrogen for 50 min to deoxygenate, heat to 94 ° C, add 5 g of secondary amine nano-silica, continue to heat to 145 ° C to react for 10 h, and after the reaction is completed, remove the solvent by rotary evaporation to obtain tertiary amine nano-silica modified pyrrolidone; (5) Add 6.5 g of 1,3-propane sultone to 65 mL of acetone solvent, stir and dissolve at 32 °C, dissolve 4.8 g of tertiary amine nano-silica-modified pyrrolidone in 30 mL of acetone, and add it dropwise to the 1,3-propane sultone solution for 45 min. After the addition is complete, heat to 40 °C and react for 5 h. After the reaction is complete, filter and dry to obtain a zwitterionic monomer. (6) Add 15 g of lignite to 30 mL of 5.2% sodium hydroxide solution, heat to 95 °C and stir for 2 h, then filter out the insoluble residue to obtain lignite alkali solution; (7) Add 14 mL of lignite alkali solution, 1.1 g of acrylamide, 0.6 g of modified benzoxazine monomer, and 0.5 g of zwitterionic monomer into a flask, stir and mix, introduce nitrogen for 12 min to deoxygenate, heat to 51 °C, add 0.08 g of ammonium persulfate, continue to heat to 66 °C and react for 2.5 h. After the reaction is completed, a lignite graft copolymer is obtained; (8) 16 parts by weight of lignite graft copolymer, 1.5 parts by weight of hydroxypropyl cellulose, and 0.3 parts by weight of graphene oxide were added to a reactor, and the mixture was stirred at 800 rpm for 16 min. The mixture was dried in a drying oven at 70° C. and then crushed to obtain a lignite-based modified fluid loss reducer for drilling fluid. Example 5

[0020] (1) Add 11 g of 2-alkenyl-4-aminopyridine and 5.9 g of polyformaldehyde to 60 mL of toluene solvent, react at 34 °C for 0.7 h, add 11.6 g of p-hydroxybenzaldehyde, heat to 80 °C and reflux for 5.5 h. After the reaction, wash with 4.2% sodium hydroxide aqueous solution, and remove the solvent by rotary evaporation to obtain intermediate 1; (2) Add 2.3 g of melamine, 7 g of intermediate 1, and 3 g of anhydrous sodium sulfate dehydrating agent to 42 mL of methanol solvent, introduce nitrogen protection, heat to 110° C. and react for 4.5 h. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a modified benzoxazine monomer; (3) 45 mL of anhydrous ethanol and 15 mL of deionized water were mixed as a solvent, 9 g of N-ethyl-3-trimethoxysilane-2-methylpropylamine was added thereto, and ultrasonic dispersion was performed for 40 min. 2.7 mL of a 2.8% hydrochloric acid solution was added to adjust the pH value to 4.5, 2.2 g of nano-silica was added, and ultrasonic dispersion was performed for 1.2 h. The mixture was heated to 75 °C and refluxed for 4 h. After the reaction was completed, the mixture was washed with anhydrous ethanol, filtered and dried to obtain secondary amine nano-silica. (4) Add 8 g of N-vinyl pyrrolidone, 5 g of polyformaldehyde, and 0.02 g of acetic acid catalyst to 70 mL of anhydrous ethanol solvent, stir and mix, introduce nitrogen for 30 min to deoxygenate, heat to 88 ° C, add 4.2 g of secondary amine nano-silica, continue to heat to 135 ° C to react for 6 h, and after the reaction is completed, remove the solvent by rotary evaporation to obtain tertiary amine nano-silica modified pyrrolidone; (5) Add 4.5 g of 1,3-propane sultone to 45 mL of acetone solvent, stir and dissolve at 28 °C, dissolve 3.2 g of tertiary amine nano-silica-modified pyrrolidone in 20 mL of acetone, and add it dropwise to the 1,3-propane sultone solution for 30 min. After the addition is complete, heat to 35 °C and react for 3.5 h. After the reaction is complete, filter and dry to obtain a zwitterionic monomer; (6) Add 10 g of lignite to 20 mL of 4.8% sodium hydroxide solution, heat to 80 °C and stir for 1 h, then filter out the insoluble residue to obtain lignite alkali solution; (7) Add 18 mL of lignite alkali solution, 1.4 g of acrylamide, 0.8 g of modified benzoxazine monomer, and 0.6 g of zwitterionic monomer into a flask, stir and mix, introduce nitrogen for 15 min to deoxygenate, heat to 54 °C, add 0.09 g of ammonium persulfate, continue to heat to 70 °C and react for 3 h. After the reaction is completed, a lignite graft copolymer is obtained; (8) 18 parts by weight of lignite graft copolymer, 1.8 parts by weight of hydroxypropyl cellulose, and 0.4 parts by weight of graphene oxide were added to a reactor, stirred and mixed at 900 rpm for 20 min, dried in a drying oven at 72° C., and then crushed to obtain a lignite-based modified fluid loss reducer for drilling fluid.

[0021] Comparative Example 1 The difference between this comparative example and Example 1 is that step (7) does not contain modified benzoxazine monomer.

[0022] Comparative Example 2 The difference between this comparative example and Example 1 is that step (7) does not contain zwitterionic monomer.

[0023] Referring to SY / T5241-91 "Evaluation Procedure for Fluid Loss Reducers for Water-Based Drilling Fluids", freshwater drilling fluid base slurry was prepared. The specific preparation method was as follows: 1000 mL of tap water was added with 4.0% bentonite by mass, followed by 30 g of sodium carbonate, and stirred at 8000 rpm for 20 min to obtain freshwater drilling fluid base slurry.

[0024] Take 400mL of freshwater drilling fluid base slurry, add 1.2% of filtrate reducer, add different amounts of sodium chloride to the system, cure at room temperature for 16 hours, and measure the API medium pressure filtration loss of the drilling fluid. The test results are shown in Table 1.

[0025] Table 1: Salt resistance test.

[0026]

[0027] It can be seen from Table 1 that the filtrate reducer in Examples 1-5 can still maintain a lower filtration loss under high-salinity conditions than the filtrate reducer in Comparative Examples 1-2, and has better salt resistance.

[0028] Take 400mL of freshwater drilling fluid base slurry, add 1.2% of filtrate reducer, and cure at different temperatures for 16h to measure the API medium pressure filtration loss of the drilling fluid. The test results are shown in Table 2.

[0029] Table 2: Temperature resistance test.

[0030]

[0031] It can be seen from Table 2 that the filtrate reducer in Examples 1-5 can still maintain a lower filtration loss under high temperature conditions than the filtrate reducer in Comparative Examples 1-2, and has better heat resistance.

[0032] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well.

Claims

1. A lignite-based modified fluid loss reducer for drilling fluid, characterized in that: The invention comprises the following components by weight: 14-18 parts by weight of lignite graft copolymer, 1.2-1.8 parts by weight of hydroxypropyl cellulose and 0.2-0.4 parts by weight of graphene oxide.

2. The lignite-based modified fluid loss reducer for drilling fluid according to claim 1, characterized in that: The method for preparing the lignite graft copolymer comprises the following steps: (1) Add 10-12 g of 2-alkenyl-4-aminopyridine and 5.6-6.2 g of polyformaldehyde to 50-70 mL of toluene solvent, react at 30-38° C. for 0.5-1 h, add 10.8-12.4 g of p-hydroxybenzaldehyde, heat to 75-85° C. and reflux for 4-7 h. After the reaction, wash with a sodium hydroxide aqueous solution having a mass fraction of 4%-4.5%, and remove the solvent by rotary evaporation to obtain intermediate 1; (2) Add 2.1-2.5 g of melamine, 6.5-7.5 g of intermediate 1, and 2.8-3.2 g of a dehydrating agent to 35-50 mL of methanol solvent, introduce nitrogen protection, heat to 105-115° C. and react for 3-6 hours. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a modified benzoxazine monomer; (3) 30-60 mL of anhydrous ethanol and 10-20 mL of deionized water are mixed as a solvent, 7.6-10.4 g of N-ethyl-3-trimethoxysilane-2-methylpropylamine is added thereto, ultrasonic dispersion is performed for 30-50 min, 2.4-3 mL of hydrochloric acid solution is added to adjust the pH value to 4-5, 1.8-2.6 g of nano-silica is added, ultrasonic dispersion is performed for 1-1.5 h, the temperature is raised to 70-80 ° C and refluxed for reaction for 2-6 h, after the reaction is completed, the mixture is washed with anhydrous ethanol, filtered and dried to obtain secondary amine nano-silica; (4) Add 8-12 g of N-vinyl pyrrolidone, 5-7 g of polyformaldehyde, and 0.02-0.05 g of a catalyst to 70-80 mL of anhydrous ethanol solvent, stir and mix, introduce nitrogen for 30-50 min to deoxygenate, heat to 88-94° C., add 4.2-5 g of secondary amine nano-silica, continue to heat to 135-145° C. and react for 6-10 h. After the reaction is completed, remove the solvent by rotary evaporation to obtain tertiary amine nano-silica modified pyrrolidone; (5) Add 4.5-6.5 g of 1,3-propane sultone to 45-65 mL of acetone solvent, stir and dissolve at 28-32° C., dissolve 3.2-4.8 g of tertiary amine nano-silica-modified pyrrolidone in 20-30 mL of acetone, and add it dropwise to the 1,3-propane sultone solution. After the addition is complete, heat to 35-40° C. and react for 3.5-5 hours. After the reaction is complete, filter and dry to obtain a zwitterionic monomer; (6) Add 10-18 mL of lignite alkali solution, 0.8-1.4 g of acrylamide, 0.5-0.8 g of modified benzoxazine monomer, and 0.4-0.6 g of zwitterionic monomer into a flask, stir and mix, introduce nitrogen for 10-15 min to deoxygenate, raise the temperature to 48-54°C, add 0.07-0.09 g of ammonium persulfate, continue to raise the temperature to 62-70°C, react for 2-3 h, and after the reaction is completed, obtain a lignite graft copolymer.

3. The lignite-based modified fluid loss reducer for drilling fluid according to claim 2, characterized in that: The dehydrating agent in step (2) is anhydrous sodium sulfate.

4. The lignite-based modified fluid loss reducer for drilling fluid according to claim 2, characterized in that: The mass fraction of the hydrochloric acid solution in step (3) is 2.6%-3%.

5. The lignite-based modified fluid loss reducer for drilling fluid according to claim 2, characterized in that: In the step (4), the catalyst is acetic acid.

6. The lignite-based modified fluid loss reducer for drilling fluid according to claim 2, characterized in that: The dripping time of the tertiary amine-based nano-silica-modified pyrrolidone in step (5) is 30-45 minutes.

7. The lignite-based modified fluid loss reducer for drilling fluid according to claim 2, characterized in that: The preparation method of the lignite alkali solution in step (6) is as follows: add 10-15 g of lignite to 20-30 mL of a sodium hydroxide solution having a mass fraction of 4.8%-5.2%, heat to 80-95° C., stir for 1-2 h, and then filter to remove insoluble residue to obtain the lignite alkali solution.

8. A method for preparing the lignite-based modified fluid loss reducer for drilling fluid according to any one of claims 1 to 7, characterized in that: The preparation method of the lignite-based modified fluid loss reducer for drilling fluid comprises the following steps: adding lignite graft copolymer, hydroxypropyl cellulose and graphene oxide into a reactor, stirring and mixing at 700-900 rpm for 12-20 minutes, drying in a drying oven at 68-72° C. and then crushing to obtain the lignite-based modified fluid loss reducer for drilling fluid.

Citation Information

Patent Citations

  • High-temperature-resistant salt-resistant polymer filtrate reducer used in water-based drilling fluid and preparation method thereof

    CN104388061A

  • Temperature-resistant and salt-tolerant high-efficiency filtrate reducer for drilling fluid and preparation method thereof

    CN112876606A

  • Temperature-resistant and salt-resistant water-based drilling fluid filtrate reducer and preparation method thereof

    CN113150754A

  • Nitrile-ketone copolymer filtrate reducer for drilling fluid and preparation method of nitrile-ketone copolymer filtrate reducer

    CN116162213A

  • High-temperature-resistant salt-resistant filtrate reducer as well as preparation method and application thereof

    CN118255954A

Cited By

  • Sulfonated lignite applied to drilling fluid and preparation method thereof

    CN120924244A

  • Sulfonated lignite applied to drilling fluid and preparation method thereof

    CN120924244B

  • Lubricant for drilling fluid and preparation method thereof

    CN121136691A

  • Graft modified cellulose filtrate reducer and preparation method thereof

    CN121343078A

  • Sulfonated asphalt for drilling fluid and preparation method thereof

    CN121759179A